ON POLARIZATION PARAMETERS VARIABILITY OF OBSERVED GALACTIC RADIO EMISSION - Kovalchuk, O. M.; Razin, V. A.; Teplykh, A. I. (Одеські астрономічні публікації, 2017)
Correlations between the solar activity and the observed polarization of the galactic radio emission are discussed.